2019
DOI: 10.1007/s42770-019-00158-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of overexpressed sigma factors on fermentative stress response of Zymomonas mobilis

Abstract: Zymomonas mobilis is a bacterium of industrial interest due to its high ethanol productivity and high tolerance to stresses. Although the physiological parameters of fermentation are well characterized, there are few studies on the molecular mechanisms that regulate the response to fermentative stress. Z. mobilis ZM4 presents five different sigma factors identified in the genome annotation, but the absence of sigma 38 leads to the questioning of which sigma factors are responsible for its mechanism of fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…They revealed that the expression level of sigE enhanced by 8.2 and 6-fold at pH 3.8 and in 12% ethanol, respectively. Our findings on furfural, acetic acid and multiple inhibitor compounds in sugarcane bagasse hydrolysate, along with Zhang et al (2010) outcomes on low pH and ethanol stress and Benoliel et al (2019) on high temperature, confirmed Seo's theory (2005) about the critical role of sigE in the response to various stress conditions[15,20,35].…”
supporting
confidence: 88%
See 4 more Smart Citations
“…They revealed that the expression level of sigE enhanced by 8.2 and 6-fold at pH 3.8 and in 12% ethanol, respectively. Our findings on furfural, acetic acid and multiple inhibitor compounds in sugarcane bagasse hydrolysate, along with Zhang et al (2010) outcomes on low pH and ethanol stress and Benoliel et al (2019) on high temperature, confirmed Seo's theory (2005) about the critical role of sigE in the response to various stress conditions[15,20,35].…”
supporting
confidence: 88%
“…Benoliel et al (2019) overexpressed sigE in Z. mobilis and evaluated the recombinant strain in response to high temperatures and ethanol stresses. According to their results, the overexpression of sigE led to significant improvement in high temperature tolerance, but there is no clear evidence that this sigma factor protects Z. mobilis in ethanol stress [15].…”
Section: Effect Of Furfural and Acetic Acid On Fermentation Profiles mentioning
confidence: 97%
See 3 more Smart Citations